Analysis of rainfall event and bridge on Galing River - Ahmad Fadli, Zainal Abidin (2010)
The growth of development and not well planned drainage system is one of the factors causing flooding. The development activities will affect the properties of the soil. This phenomenon will result in serious flooding to the downstream area especially when the arrival of the monsoon season. Kuantan town is one of the examples that faces this problem. Therefore, this study is to predict the flood upon the arrival of the monsoon season at the Galing River as the selected catchment area based on historical rainfall data. The data for the study included, tidal water level and river cross section. Analysis were carried out using InfoWorks RS software. From the analysis, the hydrograph were plotted as the result to show the critical water level for the some of the section of the river.